(untitled) (MAUSAM, 1998)
The dimensions of attractors of daily maximum temperature (during March-May) recorded by the two observatories of Madras, viz., Nungarnbakkarn and Meenambakkarn are estimated from phase space trajectories by the method of deterministic chaos, The dimensions provide the basic information on the minimum number of parameters required to understand the complex dynamical system and also the upper bound (degrees of freedom) of such parameters that are sufficient to model the system, The fractal dimension for the weather event, viz. maximum temperature over Madras is between 3.5 and 3.9 suggesting 4 parameters are necessary to model the system and a maximum of 19 parameters are sufficient.